Impact of adventure based training program on life effectiveness among corporate employees at Eagle Ranch Resort / Nurul Alya Mohamed Adnan - Mohamed Adnan, Nurul Alya (2017)
The purpose of this study was to examine the impact of adventure based trammg on life effectiveness before and after the corporate participants participated on the outdoor program. Hence, in this study, there were thirteen dimensions of life effectiveness and the Life Effectiveness Questionnaire (CPET-Long Version) instrument was used for the pre-treatment and post-treatment questionnaire. 129 respondents comprising males and females aged from 18 years old and above were involved by using convenience sampling technique. The results showed that the mean score for the dimensions after the participants participated in the program were CT (M=4.22, SD=.55), PR (M=4.20, SD=.54), OC (M=4.15, SD=.52), CS (M=4.08, SD=.57), SC (M=4.08, SD=.56), TM (M=4.07, SD=.55), T&E (M=4.05, SD=.56), DM (M=4.00, SD=.54), IT (M=4.00, SD=.53), LA (M=3.98, SD=.54), AO (M=3.74, SD=.44), CRS (M=3.53, SD=.41) and SA (M=3.41, SD=.59). This study was in line with the previous study that ABT program enhanced the alertness of having good connection in settled the organization tasks (Idros et al., 2012) and developed the participants' teamwork, communication and confidence level (Ndung'u, 2014). As a conclusion, ABT had positive impact and produced long term and lasting effect of life effectiveness towards the participants